Representing the Region on the Floor: Socioeconomic Characteristics of Electoral Districts and Legislative Speechmaking. Issue 1 (7th June 2017) - Bäck, Hanna; Debus, Marc
Abstract: Does it matter which electoral districts Members of Parliament (MPs) represent when participating in parliamentary debates? We suggest that the party leadership, in particular in governing parties, will try to keep MPs off the floor if they come from regions with economic problems, because such MPs are more likely to deviate from the party line. This should be especially likely when MPs are directly elected and have incentives to create a personal platform. The characteristics of the German electoral system allow for evaluating this argument. By analysing 9824 speeches in Bundestag debates focusing on economic issues and 8357 speeches held in debates on societal, foreign and education policy, we find support for our hypotheses that directly elected MPs deliver significantly fewer speeches in economic debates the worse the economic situation is in the district they represent. However, there is no clear pattern when differentiating between MPs from the government or opposition camp in terms of the number of delivered speeches in parliamentary debates.